2020
DOI: 10.4239/wjd.v11.i7.309
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between diabetic polyneuropathy, serum visfatin, and oxidative stress biomarkers

Abstract: BACKGROUND Diabetic polyneuropathy is a very common complication of diabetes. Numerous studies are available in terms of pathogenesis. But examination methods with low reliability are still not standardized and generally time consuming. High-sensitive, easy-to-access methods are expected. Biochemical markers are one of the subjects of research. We aimed to discover a potential biomarker that can be used for this purpose in patients with diabetes who have not yet developed symptoms of neuropathy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Encamps are considered to provide a way for organs to communicate [35]. Previous research by Buyukaydin et al [36] revealed no relations hip between Visfatin results and biochemical parameters, oxidative stress biomarkers, or thioldisulphide levels. Visfatin may be implicated in endothelial dysfunction, according to Alghasham and Barakat [37].…”
Section: Discussionmentioning
confidence: 99%
“…Encamps are considered to provide a way for organs to communicate [35]. Previous research by Buyukaydin et al [36] revealed no relations hip between Visfatin results and biochemical parameters, oxidative stress biomarkers, or thioldisulphide levels. Visfatin may be implicated in endothelial dysfunction, according to Alghasham and Barakat [37].…”
Section: Discussionmentioning
confidence: 99%
“…NAD is required for various processes, including metabolic processes, glucose-stimulated insulin secretion, cell survival, cell cycle control, and apoptosis[ 51 ]. However, elevated levels of visfatin have been linked to increased levels of inflammatory markers such as IL-6, IL-8, C-reactive protein, and monocyte chemotactic protein-1[ 52 , 53 ], endothelial dysfunction[ 54 ], and increase in oxidative stress[ 55 - 58 ]. These findings point to the existence of an average physiological level of visfatin at which it is properly controlled and fulfils its physiological functions, as well as a threshold level at which its pathological consequences occur.…”
Section: Physiological Versus Pathological Effects...mentioning
confidence: 99%
“…The role of oxidative stress in pathogenesis of DN was broadly evaluated previously. Increased ROS is considered as one of the factors associated with programmed cell death [ 39 ]. This is of particular importance sine ROS were observed in dorsal root ganglia and Schwann cells; thus they might play important role in the DN pathogenesis [ 39 ].…”
Section: Biochemical Changes In Diabetic Neuropathymentioning
confidence: 99%
“…Increased ROS is considered as one of the factors associated with programmed cell death [ 39 ]. This is of particular importance sine ROS were observed in dorsal root ganglia and Schwann cells; thus they might play important role in the DN pathogenesis [ 39 ]. Additionally, the oxidative stress affects the mitochondria via several mechanisms that include inhibition of ATP synthesis as well as essential proteins in to mitochondria, and affects mitochondrial membrane permeability by damaging the inner membrane proteins [ 38 ].…”
Section: Biochemical Changes In Diabetic Neuropathymentioning
confidence: 99%